Sistem Pakar Dalam Mendiagnosa Penyakit Parkinson Menerapkan Metode Dempster-Shafer - Agus Iskandar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
After Alzheimer's disease, Parkinson's disease is the most common neurodegenerative condition affecting people. Millions of people, or about 1% of the world's population, are affected by Parkinson's disease. Parkinson's disease is a neurodegenerative condition of the central nervous system that affects the motor system and develops over time. Even though Parkinson's disease is an uncommon condition, a tool is created by utilizing an expert system to identify this condition from the symptoms experienced by the patient. Based on the user's perceived trust value, the expert system generates disease opportunities. The Dempster-Shafer approach technique is used to calculate the trust value. The Dempster-Shafer approach reduces uncertainty and results in a correct diagnosis. the result of the inclusion or deletion of new data, such as details about symptoms and disease. Under this approach, specialists are valued for the knowledge they possess. This method rewards professionals for the knowledge they possess. Dempster-Shafer This investigation will use a diagnostic approach to Parkinson's disease. Based on the results of the procedure for applying the Dempster-Shafer method, it was determined that the patient showed some symptoms of Parkinson's disease, and it was determined that the patient had stage 2 Parkinson's disease with an accuracy value of 0.944 or a percentage of 94%. An expert system with the Dempster-Shafer technique can be used to diagnose Parkinson's disease in patients or users by calculating the symptoms experienced by the patient, according to the results of calculations performed manually by the system.